Procedimentalismo puro e justificação da democracia moderna : legitimação e arbitrariedade - Izquierdo, Felipe Held (2017)
I will begin by introducing the proceduralist approach, as seen in theories of justification of the democratic procedure that seek normative conditions of intrinsic value to the procedure, so that it remains, in the end, justified. The purely proceduralist approach has it that a decision-making procedure, under due democratic constrictions, confers legitimacy to its results: by means of strictly procedural conditions, i.e. equality of participation, results are considered legitimate. Thus, what needs establishing, is that, though necessary to the procedure’s justification, conditions of equal participation are not sufficient to the legitimacy of results. Although procedural conditions are indeed necessary so that there be a public justification of the procedure, there is a relevant relation between results and procedure which pure proceduralist theory wills away. The pressupositions that lead to the kind of subjective justification entailed do not exclude the necessity of there being also objective reasons on which the justification must turn. For, if not, it follows that results are being arbitrarily legitimized, due to the sufficiency of a strictly procedural claim to justification. In order to attain to the purported theoretical end of this work, I will begin by assessing different types of proceduralism, leading lastly to pure proceduralism. Leaving from the implicature relation established by this kind of proceduralism between justification and legitimation, I will present instrumentalism as the inverse relation, also displaying its faults. In the follow up and thence towards the conclusion it will be shown why subjective justification of the sort made sufficient by pure proceduralism must not be so, and why there is a need for objective reasons so that the results of a democratic procedure can be considered legitimate in non-arbitrary fashion.